Dynamic in vitro gastric digestion behavior of goat milk: Effects of homogenization and heat treatments. - Li S; Ye A; Pan Z; Cui J; Dave A; Singh H (Elsevier Inc on behalf of the American Dairy Science Association, 2022)
The gastric digestion behavior of differently processed goat milks was investigated using a dynamic in vitro gastric digestion model, the human gastric simulator. Homogenization and heat treatment of goat milk resulted in gastric clots with highly fragmented structures. They also delayed the pH reduction during digestion, altered the chemical composition of the clots and the emptied digesta, promoted the release of calcium from the clots, and accelerated the hydrolysis and the emptying of milk proteins. The apparent density of the protein particles and the location of the homogenized fat globules changed during the digestion process, as shown in the emptied digesta of the homogenized goat milks. The effects of processing on the digestion behavior of goat milk were broadly similar to those previously reported for cow milk. However, the overall gastric digestion process of goat milk was more affected by homogenization than by heat treatments.
Keywords: gastric digestion; goat milk; heat treatment; homogenization; protein hydrolysis; Animals; Cattle; Digestion; Female; Goats; Hot Temperature; Milk; Milk Proteins